A model pile load test in laterite soil / Mohd Haroma Ismail - Ismail, Mohd Haroma (1996)
This model study on Bearing Capacity and Settlement of single pile in Laterite soil was performed to check on the Ultimate Bearing Capacity and Settlement as calculated by various theoretical methods against actual values obtained by loading test. In order to achieve a comprehensive assessment on both parameters, especially the settlement behaviour, the loading test was documented to produce a relationship between Load and Settlement. From this study, it was found that for Ultimate Bearing Capacity, the available theoretical methods predict with reasonable accuracy especially for Tomlinson's Method and Vijayvergjva Method. As for settlement, the aggrement between calculated and measured settlement are poor.